Altered resting-state connectivity in adolescent cannabis users. (4th November 2013) - Orr, Catherine; Morioka, Rowen; Behan, Brendan; Datwani, Sameer; Doucet, Marika; Ivanovic, Jelena; Kelly, Clare; Weierstall, Karen; Watts, Richard; Smyth, Bobby; Garavan, Hugh
Abstract: Background : Cannabis is the most commonly used illicit drug in adolescence. Heavy use is associated with deficits on a broad range of cognitive functions and heavy use during adolescence may impact development of gray and white matter. Objectives : To examine differences in intrinsic brain activity and connectivity associated with cannabis dependence in adolescence using whole-brain voxelwise approaches. Methods : Adolescents admitted to a drug-treatment facility for cannabis dependence ( n = 17) and age-matched controls ( n = 18) were compared on a measure of oscillations in the low-frequency blood oxygen level-dependent signal at rest (the fractional amplitude of low-frequency fluctuations fALFF, 0.01–0.1 Hz) and interhemispheric resting-state functional connectivity (RSFC) using voxel-mirrored homotopic connectivity. Results : The cannabis-dependent population showed increased fALFF activity compared to the control group in right hemisphere regions including the superior parietal gyrus, superior frontal gyrus, inferior frontal gyrus, inferior semilunar lobe of the cerebellum and the inferior temporal gyrus. Post-hoc analyses revealed stronger intra-hemispheric functional connectivity between these functionally defined regions of interest (ROIs) in the cannabis-dependent population than in the controls. Reduced interhemispheric connectivity was observed in the cannabis users compared to controls in the pyramis of the cerebellum and the superior frontal gyrus. Controls showed reduced interhemispheric connectivity compared to users in the supramarginal gyrus. Conclusions : The reduced interhemispheric RSFC in adolescent cannabis users complements previous reports of white matter deficits associated with cannabis use. The evidence of elevated connectivity within the right hemisphere may reflect a compensatory mechanism. Combined, the results suggest that altered intrinsic connectivity may be characteristic of adolescent cannabis dependence.